Pelatihan Rich Task Pada Mgmp Matematika SMP Lombok Barat - Ita Chairun Nissa; I Ketut Sukarma; Sanapiah Sanapiah; Ade Kurniawan; Sabrun Sabrun (Abdi Masyarakat, 2020)
The West Lombok Mathematics’ Teacher Community needs to be improved because of the government's demands on the quality of teaching mathematics in schools. Having good mathematical knowledge and being able to solve real-life problems is an important key for teachers to be able to develop innovative mathematics teaching. But in fact, teacher training that emphasizes aspects of mathematical content is still not widely implemented. This is an important reason for this training. The training is carried out in one day through video screening and rich task modeling. The assessment of this training is measured using a closed questionnaire that asks the teacher's attitude towards statements related to the training material, training methods, the ability of the speakers, and the motivation of the trainees. The training that was carried out succeeded in getting a positive response that most of the teachers gave a very agreeing attitude. The teachers also feel motivated and have good expectations for applying the knowledge and skills gained from training into teaching mathematics in the classroom